Ganglioneuroma presenting as an adrenal incidentaloma: a case report - Adas, Mine (BioMed Central, 2014)
INTRODUCTION: Ganglioneuromas are rare benign tumors arising from the neural crest tissue and are most commonly located in the posterior mediastinum and retroperitoneum; they are rarely found in the adrenal gland. This tumor is usually asymptomatic and in the majority of cases is detected incidentally. Although the characteristics of adrenal ganglioneuroma on computerized tomography and magnetic resonance imaging have been well described, the exact diagnosis is difficult. Histopathological examination is currently the mainstay of diagnosis. Ganglioneuromas have a very good prognosis with surgical removal. We report the case of a male patient with an incidentally identified adrenal ganglioneuroma with high standardized uptake values in a positron emission tomography scan. CASE PRESENTATION: An 18-year-old Turkish male patient with no previous comorbidities was admitted to our hospital with lower-quadrant pain. He had no significant past medical or surgical history. A physical examination did not reveal any signs and the results of routine laboratory tests were all within the normal ranges. Our patient underwent computed tomography of his abdomen, which showed a relatively homogenous left adrenal tumor measuring 5.2×4.3×7.1cm. On a positron emission tomography scan, the left adrenal gland disclosed a standardized uptake value of 4.1. Our patient underwent an exploratory laparotomy with left adrenalectomy without any related complications. CONCLUSION: Ganglioneuroma may sometimes be similar to other adrenal malignancies. Careful evaluation with endocrine tests and imaging procedures is necessary to provide an accurate diagnosis. Definitive diagnosis can be made by histological examination. The prognosis is very good with surgical removal.